A constructive bandwidth reduction algorithm. (8th October 2012) - Arathi, P.; Doss, L. Jones Tarcius; Kanakadurga, K.
In this paper, a viable bandwidth minimisation algorithm based on graphs, for reducing the bandwidth of sparse symmetric matrices, is presented. The algorithm is tested for various sparse symmetric matrices arising from standard structured and random graphs. Bandwidth results for these matrices are also obtained using the existing algorithms and compared. The proposed algorithm is easy to implement and the bandwidth reductions obtained with the proposed algorithm are good when compared with the existing algorithms.